2020
DOI: 10.1017/s0022149x20000693
|View full text |Cite
|
Sign up to set email alerts
|

Equines as reservoirs of human fascioliasis: transmission capacity, epidemiology and pathogenicity inFasciola hepatica-infected mules

Abstract: Fascioliasis is a zoonotic disease caused by liver flukes transmitted by freshwater lymnaeid snails. Donkey and horse reservoir roles have been highlighted in human endemic areas. Liver fluke infection in mules has received very limited research. Their role in disease transmission, epidemiological importance and Fasciola hepatica pathogenicity are studied for the first time. Prevalence was 39.5% in 81 mules from Aconcagua, and 24.4% in 127 from Uspallata, in high-altitude areas of Mendoza province, Argentina. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…The bile ducts of South American camelids show more similarity with the equine bile system than with the bile system of domestic ruminants [ 105 ]. Despite this, the histopathological picture of fascioliasis in llamas suggests a low resistance to liver fluke infection and has been reported to be more similar to that in sheep [ 99 , 100 , 106 ] than to that in equines [ 107 ]. Indeed, F. hepatica infection is a common cause of production loss and mortality in domesticated New World camelids [ 44 , 55 , 57 , 58 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bile ducts of South American camelids show more similarity with the equine bile system than with the bile system of domestic ruminants [ 105 ]. Despite this, the histopathological picture of fascioliasis in llamas suggests a low resistance to liver fluke infection and has been reported to be more similar to that in sheep [ 99 , 100 , 106 ] than to that in equines [ 107 ]. Indeed, F. hepatica infection is a common cause of production loss and mortality in domesticated New World camelids [ 44 , 55 , 57 , 58 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be considered that llamas may play a disease-spreading role if used as pack animals in rural areas ( Figure 7 D,E and Figure 8 ), as already highlighted in the case of donkeys [ 25 ] and mules [ 107 ], the latter two with a capacity to transport pronouncedly higher weights of goods [ 111 ]. Such a fascioliasis-spreading capacity poses a problem for the implementation of a One Health initiative, because pack animals may give rise to movements of the parasite and the vector from one part to another of the zone selected for control intervention, or the introduction of the parasite and/or the vector from outside into that zone.…”
Section: Discussionmentioning
confidence: 99%
“…If presenting a high immunological refractory response, liver flukes will survive less time inside that host and the contribution to transmission will consequently be restricted in quantity and time, as is the case of several cattle races. Fascioliasis is known to be different in equines and ruminants from the pathogenicity point of view, with the horse as the most resistant, the donkey as the most susceptible, and the mule showing intermediate profile although closer to those of the horse (90). Indeed, F. hepatica infection has been reported to be fatal for donkeys (86), and the pathology caused by a F. gigantica infection in donkeys has already been analyzed post-mortem in Egypt (91).…”
Section: Epidemiological Role Of the Donkeymentioning
confidence: 99%
“…In mules, it was observed that a massive infection by 97 adult flukes was highly pathogenic and finally fatal, and that the maximum daily output was 794,500 eggs/mule/day (90).…”
Section: Epidemiological Role Of the Donkeymentioning
confidence: 99%
See 1 more Smart Citation